A randomized trial of adoptive immunotherapy with tumor‐infiltrating lymphocytes and interleukin‐2 versus standard therapy in the postoperative treatment of resected nonsmall cell lung cancer - Ratto, Giovanni B.; Zino, Paolo; Mirabelli, Sandro; Minuti, Paolo; Aquilina, Riccardo; Fantino, Giovanni; Spessa, Elisabetta; Ponte, Marco; Bruzzi, Paolo; Melioli, Giovanni (Cancer, 1996)
BACKGROUND A previous pilot study from our group suggested that: 1) adoptive immunotherapy (AI) with Tumor Infiltrating Lymphocytes (TIL) and recombinant Interleukin‐2 (rIL‐2) may be applied with safety in more than 80% of patients operated upon for stage III NSCLC, and 2) AI could be useful in patients with locally advanced disease. The present randomized study was planned to assess the efficacy of AI in the postoperative treatment of stage II, IIIa or IIIb NSCLC. METHODS TIL were “in vitro” expanded from tissue samples obtained from surgically removed specimens in 131 patients. Eighteen cultures yielded no growth of TIL. The remaining 113 patients were stratified according to the disease stage and randomized to receive AI or standard chemo‐radiotherapy. TIL were infused i.v., 6 to 8 weeks after surgery. IL‐2 was administered subcutaneously at escalating doses for 2 weeks, and then at reduced doses for 2–3 months. RESULTS Three‐year survival was significantly better (P < 0.05) in patients who underwent AI than in control patients. AI was of no benefit to subjects with stage II NSCLC, potentially useful to subjects with stage IIIa NSCLC (P = 0.06) and significantly advantageous to subjects with stage IIIb (T4) NSCLC (P < 0.01). In patients with stage III NSCLC, local relapse (but not distant relapse) was significantly (P < 0.05) reduced following AI. CONCLUSIONS AI should be taken into consideration when designing future adjuvant therapy protocols for NSCLC treatment. Cancer 1996;78:244‐51.